JUMPptm: Integrated software for sensitive identification of post‐translational modifications and its application in Alzheimer's disease study. Issue 3 (20th September 2022) - Poudel, Suresh; Vanderwall, David; Yuan, Zuo‐Fei; Wu, Zhiping; Peng, Junmin; Li, Yuxin
Abstract: Background : Mass spectrometry (MS)‐based proteomic analysis of posttranslational modifications (PTMs) usually requires the pre‐enrichment of modified proteins or peptides. However, recent ultra‐deep whole proteome profiling generates millions of spectra in a single experiment, leaving many unassigned spectra, some of which may be derived from PTM peptides. Methods : Here we present JUMPptm, an integrative computational pipeline, to extract PTMs from unenriched whole proteome. JUMPptm combines the advantages of JUMP, MSFragger and Comet search engines, and includes de novo tags, customized database search and peptide filtering, which iteratively analyzes each PTM by a multi‐stage strategy to improve sensitivity and specificity. Results : We applied JUMPptm to the deep brain proteome of Alzheimer's disease (AD), and identified 34, 954 unique peptides with phosphorylation, methylation, acetylation, ubiquitination, and others. The phosphorylated peptides were validated by enriched phosphoproteome from the same sample. TMT‐based quantification revealed 482 PTM peptides dysregulated at different stages during AD progression. For example, the acetylation of numerous mitochondrial proteins is significantly decreased in AD. A total of 60 PTM sites are found in the pan‐PTM map of the Tau protein. Conclusion : The JUMPptm program is an effective tool for pan‐PTM analysis and the resulting AD pan‐PTM profile serves as a valuable resource for AD research.